Photocatalytic degradation and upcycling of nitrate-rich textile wastewater to ammonia over a tandem reactor - Huimei Zhang; Hong Liu; Wenwen Zhang; Lijuan Wang; Wenxi Qiu (Scientific Reports)
Abstract Textile is one of the industrial sectors producing multiple types of polluting substances, including dyes and nitrate. Lately, the realization of pollutant degradation through electrochemical treatment has been applied more commonly. However, in textile wastewater a high level of organic dyes can inhibit the electrocatalytic reduction of nitrate. Hence, we construct a tandem reactor to synchronously remove the organic dyes and nitrate contaminants as well as yield the value-added ammonia product from the simulated textile wastewater. The tandem reactor shows impressive efficiency towards photocatalytic decomposing methylene blue (MB), methyl orange (MO) and methyl violet (MV) (~ 100%) coupled with NO3 −-to-NH3 conversion (maximum NH3 evolution value of 44.3 μg cm−2) under different bias potentials. Liquid chromatography mass spectroscopy (LC–MS) has been applied to understand the dyes degradation pathways. The dyes are oxidized by active species hydroxyl radicals ·OH and h + under irradiation. The electrons are transferred to the cathode for nitrate reduction. In addition, the tandem reactor displays favorable energy consumption for the simulated textile wastewater treatment. Moreover, mung bean germination experiments were complemented for toxicity assessment of the system. This study presents a conceptual tandem reactor for the synergistic regulation of complex pollutants removal processes, highlighting the potential of photoelectrochemical (PEC) and electrochemical catalysis coupled to advance sustainable wastewater management technologies.